Abundance and Diversity of Phytoplankton in Mangrove Forest Waters of Aek Horsik Village, Central Tapanuli - Batubara, Lenni Wahyuni; Sinaga, Henry; Hutagalung, Desi Indriani Dameria (Journal of Coastal and Ocean Sciences, 2024)
Phytoplankton are organisms that live floating in water. Its ability to move is limited, so the organism is always carried away. The waters of mangrove forests in Tapanuli Tengah Regency are directly adjacent to the shoreline, where phytoplankton always follow the current. At high tide, phytoplankton are carried by currents to mangrove forests; at low tide, phytoplankton can be carried by currents to free ocean waters. This study aims to determine the type of phytoplankton, phytoplankton abundance, and the level of phytoplankton diversity in the Mangrove Forest Waters of Aek Horsik Village, Tapanuli Tengah Regency. This research will be conducted from May to June 2023. Phytoplankton samples were taken using the purposive sampling method, and the research station was divided into 3. Station 1 is upstream of the mangrove forest, station 2 is in the middle of the mangrove forest, and station 3 is downstream. The results of this study showed that phytoplankton found in the waters of the Mangrove Forest, Aek Horsik Village, Tapanuli Tengah Regency consisted of 5 classes totaling 15 species, namely: Class Cyanophyceae (Synedra sp), Class Euglenophyceae (Euglena viridis sp, E.protista, and Euglena sp), Class Chlorophyceae (Ankistrodesmus sp, Scenedesmus sp, Tetraedron caudatum, Closterium acutum), Class Baciliarophyceae (Navicula sp, Nitzchia sp, Tabellaria sp, Nitzchia sigma), and Class Zygnematophyceae (Cosmarium sp, Staurastrum sp, S. curvacum). The highest phytoplankton abundance was 6100 Ind/L. Phytoplankton diversity is in the medium category, with the highest value being 2.671